OC-052 A CHANGE IN PRESENTATION OF PARAOESOPHAGEAL HIATUS HERNIA REQUIRING SURGICAL INTERVENTION IN A DISTRICT GENERAL HOSPITAL IN THE NORTHERN REGION OF THE UNITED KINGDOM. (13th October 2022) - Chen, E; Ng, C E; Toumi, Z
Abstract: Aim: The incidence of paraoesphageal hiatus hernia (PEH) has changed over the last several years. This study aims to ascertain the difference in the presentation of PEH requiring operative intervention at our unit because of the COVID-19 pandemic Material & Methods: We conducted a retrospective review of procedures performed by a single surgeon for PEH in a district general hospital. We compared cases from 2016 to March 2020 and during the initial period of the COVID-19 pandemic in 2020. Results: 39 consecutive cases were identified undergoing PEH related procedures. The median age was 66 (IQR 26), with slight female predominance (M:F ratio of 5:6). 28 cases (71.8%) were performed as elective cases. After the 2020 March lockdown, there were 10 cases of PEH repair performed with 78% performed as emergency procedures, compared to 30 cases in the preceding 5 years and 10% performed as emergency cases. Chi-square test to examine the association between COVID-19 pandemic and emergency procedure, X 2 (1, N=39)=14.199, p=0.000164. Pre-COVID19 the types of procedures included 76.7% were fundoplication with suture crural closure, 10% were fundoplication with mesh repair, 3.3% biological mesh repair, 3.3% with suture closure of the crural and 6.7% had suture gastropexy. During the COVID-19 period, 44.4% were gastropexy, 33.3% were gastrostomy tube insertion and 22.2% fundoplication performed. Conclusion: We have seen significantly more emergency PEH related procedures performed and using a variety of procedures. This leads to the consideration of whether current emergency general surgery training can equip trainees for future independent practice.